2017
DOI: 10.1097/wnp.0000000000000399
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude-Integrated EEG and Brain Sparing in Preterm Small-for-Gestational-Age Infants

Abstract: The results of our study suggest that SGA infants with a good prognosis have a more mature aEEG pattern than preterm adequate-for-gestational-age patients with the same outcome. These findings support the brain sparing theory in SGA infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Some aEEG studies conducted in neonates with IUGR have been associated with brain function immaturity. 7,8,29 Our results provide new data, until now unreported, that contribute to a better knowledge on brain function maturation in these children. The analysis of the well-recognized EEG patterns of maturity in the clinical setting such as discontinuity, delta brushes, IBI duration, asymmetry, asynchrony or transients may have clinical relevance on the evaluation of SGA neonates.…”
Section: Visual Analysissupporting
confidence: 52%
See 1 more Smart Citation
“…Some aEEG studies conducted in neonates with IUGR have been associated with brain function immaturity. 7,8,29 Our results provide new data, until now unreported, that contribute to a better knowledge on brain function maturation in these children. The analysis of the well-recognized EEG patterns of maturity in the clinical setting such as discontinuity, delta brushes, IBI duration, asymmetry, asynchrony or transients may have clinical relevance on the evaluation of SGA neonates.…”
Section: Visual Analysissupporting
confidence: 52%
“…[7][8][9][10][11]30,31 However, contributions in SGA babies are more limited. In premature infants with IUGR, it has been described: (1) greater relative power in δ, and lower in θ, α and β frequency bands in relation to those non-IUGR, and (2) the relative power in the δ decreases with the increase of GA. 12,13,29 In term infants, SGA neonates have been reported to have a maturational delay, defined as power spectrum increased in δ. 14 In the present work, SGA infants, compared to AGA controls, showed higher values in the power spectrum of frequencies faster (α and β) and lower in the δ.…”
Section: Spectral Analysismentioning
confidence: 99%
“…They also spend up to 90% of their time sleeping (Ardura et al, 1995) whereas the full‐term neonate sleeps approximately 70% of the time (Mirmiran et al, 2003). Preterm infants are also reported to be at risk for impaired cognitive development with lower Apgar scores (Benavente‐Fernández et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the weeks following preterm birth, IUGR infants reportedly have altered EEG and amplitude integrated EEG, which has been correlated with poor neuromotor development (223, 224). In contrast, another study found that the subset of stable preterm IUGR with good clinical indices had more mature EEG patterns compared to the AGA peers (225), and similarly, preterm IUGR infants had accelerated EEG power spectrum maturation compared to preterm AGA controls at 1 month post-term equivalent age (226). However, no differences were observed at 6 months' post-term age between preterm IUGR and AGA infants, or in comparison to a term AGA group, suggesting such changes may resolve with time (226).…”
Section: Overcoming the Hurdles To Progressmentioning
confidence: 93%